2013
DOI: 10.1186/1477-7827-11-113
|View full text |Cite
|
Sign up to set email alerts
|

Follicular expression of follicle stimulating hormone receptor variants in the ewe

Abstract: BackgroundSeveral alternatively-spliced mRNA transcripts of the follicle stimulating hormone receptor (FSHR) have been identified in sheep, including FSHR-1 (G protein-coupled form), FSHR-2 (dominant negative form), and FSHR-3 (growth factor type-1 form). Our objective was to determine which of these variants is predominantly expressed in follicles collected from ewes at various times after estrus.MethodsSuffolk-cross ewes (n = 8) were allowed to come into estrus naturally and were euthanized 24 (n = 3), 36 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
6
15
0
Order By: Relevance
“…These findings demonstrated that FRBI treatment could decrease the mRNA and protein expression levels of FSHR and LHR in sheep COCs. Our outcomes were similar to early reports [27, 28]. These findings need to be further verified in the future.…”
Section: Discussionsupporting
confidence: 81%
“…These findings demonstrated that FRBI treatment could decrease the mRNA and protein expression levels of FSHR and LHR in sheep COCs. Our outcomes were similar to early reports [27, 28]. These findings need to be further verified in the future.…”
Section: Discussionsupporting
confidence: 81%
“…However, FSH had no obvious influence on the expression of GnRHR mRNA. The outcomes were in agreement with the report of Sullivan et al (2013).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the well characterized G protein-coupled form of the FSHR, alternatively spliced variants of the FSHR may participate in follicular dynamics during follicular waves of the sheep estrous cycle. These results revealed that FSHR-3 is the predominant form of the FSHR in sheep [14]. Therefore, FSHR-3 may be important in promoting mitotic activity and cell growth [21].…”
Section: Molecular Characteristics Of Fshr and Its Isoformsmentioning
confidence: 99%
“…However, only FSHR-1 and FSHR-3 are known to have biological functions [9]. Another variant exists that consists of a transcript encoding only exons 1-8 [13,14]. A few other heterogeneous FSHR variants have been detected in the animal species, including humans [15,16,17].…”
Section: Molecular Characteristics Of Fshr and Its Isoformsmentioning
confidence: 99%